2022
DOI: 10.6007/ijarbss/v12-i6/13157
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Graphic Stories as Indicators of Creative Thinking and Literacy Level among Malaysian Secondary School Students

Abstract: With the current uncertainties of future employment and Malaysian poor literacy rates, effective reading activities, which embed creative thinking, must be reconsidered in teaching and learning. While studies on creative thinking and assessment are available, none considered graphic stories as an assessment of creativity. Based on two short stories, graphic stories produced by secondary school students are assessed for creativity using a rubric of creativity. The assessment consists of four -Novelty, Utility, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Besides, Bakar et al (2020) also mentioned that most learners found that graphic novels helped them to expand their vocabularies and better comprehend the text. Learners were also seen to be drawn to the graphics in the literature text, which increases their enthusiasm for learning literature in the classroom that could indirectly address the motivation and engagement issues among learners, particularly those with low proficiency levels or learning disabilities as graphic novels are proven to be a fun learning activity (Fenty & Brydon, 2020;Mohamad et al, 2022). Furthermore, literature can be learned through the use of picture books, which are a type of book with paintings and a limited number of writings.…”
Section: Multimodal Mediummentioning
confidence: 99%
“…Besides, Bakar et al (2020) also mentioned that most learners found that graphic novels helped them to expand their vocabularies and better comprehend the text. Learners were also seen to be drawn to the graphics in the literature text, which increases their enthusiasm for learning literature in the classroom that could indirectly address the motivation and engagement issues among learners, particularly those with low proficiency levels or learning disabilities as graphic novels are proven to be a fun learning activity (Fenty & Brydon, 2020;Mohamad et al, 2022). Furthermore, literature can be learned through the use of picture books, which are a type of book with paintings and a limited number of writings.…”
Section: Multimodal Mediummentioning
confidence: 99%